Problems and prospects of economic integration in West Africa - Plessz, Nicolas G. (Montreal, published for the Centre [for Developing-Area Studies] by McGill University Press, 1968)
The author gives an analysis of the 'integration' problem in both the English and French-speaking regions of West Africa.
Includes bibliographical references..
osc 05/09/16
Loans
Keywords: Economic integration; International Organisation; Africa, West